Structural characterization and anticoagulant activity of a sulfated polysaccharide from the green alga Codium divaricatum. (5th May 2015) - Li, Na; Mao, Wenjun; Yan, Mengxia; Liu, Xue; Xia, Zheng; Wang, Shuyao; Xiao, Bo; Chen, Chenglong; Zhang, Lifang; Cao, Sujian
Highlights: A pyruvated galactan sulfate CP2-1 was isolated from green alga Codium divaricatum . Backbone of CP2-1 consisted of galactopyranose residues with a small degree of branching. Pyruvate formed ﬁve-membered cyclic ketals with O-3 and O-4 of galactose residues. CP2-1 possessed a high anticoagulant activity in vitro . Abstract: A sulfated polysaccharide, designated CP2-1, was isolated from the green alga Codium divaricatum by water extraction and purified by anion-exchange and size-exclusion chromatography. CP2-1 is a galactan which is highly sulfated and substituted with pyruvic acid ketals. On the basis of chemical and spectroscopic analyses, the backbone of CP2-1 was mainly composed of (1→3)-β-d -galactopyranose residues, branched by single (1→)-β-d -galactopyranose units attached to the main chain at C-4 positions. The degree of branching was estimated to be about 12.2%. Sulfate groups were at C-4 of (1→3)-β-d -galactopyranose and C-6 of non-reducing terminal galactose residues. In addition, the ketals of pyruvic acid were found at 3, 4- of non-reducing terminal galactose residues forming a five-membered ring. CP2-1 possessed a high anticoagulant activity as assessed by the activated partial thromboplastin time and thrombin time assays. The investigation demonstrated that CP2-1 was an anticoagulant-active sulfated polysaccharide distinguishing from other sulfated polysaccharides from marine green algae.